The Effects of Attentional Engagement on Route Learning Performance in a Virtual Environment: An Aging Study - Hartmeyer, Steffen; Grzeschik, Ramona; Wolbers, Thomas; Wiener, Jan M. (Frontiers in Aging Neuroscience, 2017)
Route learning is a common navigation task affected by cognitive aging. Here we present a novel experimental paradigm to investigate whether age-related declines in executive control of attention contributes to route learning deficits. A young and an older participant group was repeatedly presented with a route through a virtual maze comprised of twelve decision points (DP) and non-decision points (non-DP). To investigate attentional engagement with the route learning task, participants had to respond to auditory probes at both DP and non-DP. Route knowledge was assessed by showing participants screenshots or landmarks from DPs and non-DPs and asking them to indicate the movement direction required to continue the route. Results demonstrate better performance for DPs than for non-DPs and slower responses to auditory probes at DPs compared to non-DPs. As expected we found slower route learning and slower responses to the auditory probes in the older participant group. Interestingly, differences in response times to the auditory probes between DPs and non-DPs can predict the success of route learning in both age groups and may explain slower knowledge acquisition in the older participant group.